2018
DOI: 10.3391/mbi.2018.9.2.08
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of small-scale lionfish removals as a management strategy: effort, impacts and the response of native prey and piscivores

Abstract: The live marine baitworm trade harvests, packages, and ships polychaete worms and packing algae (wormweed) from Maine, USA to consumers globally, inadvertently transferring numerous invertebrates that naturally occur in the algal habitat. Here, we use a focal taxa, the globally invasive European green crab Carcinus maenas, to examine costs associated with the successful introductions via this vector and suggest an alternative packaging, already in use in Europe. We show that restricting the use of wormweed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A lower removal efficiency, which would leave uncaptured lionfish, will need to be considered when evaluating the potential community benefits offered by lionfish trapping. Lionfish removals do not necessarily translate into ecological benefits [14,59,60], given that lionfish predation [61,62], growth [53,63], and colonization [14,51,60] rates are controlled via density-dependent feedbacks. Ecosystem models may thus be appropriate for examining the potential community effects of a deepwater lionfish fishery [15,64].…”
Section: Discussionmentioning
confidence: 99%
“…A lower removal efficiency, which would leave uncaptured lionfish, will need to be considered when evaluating the potential community benefits offered by lionfish trapping. Lionfish removals do not necessarily translate into ecological benefits [14,59,60], given that lionfish predation [61,62], growth [53,63], and colonization [14,51,60] rates are controlled via density-dependent feedbacks. Ecosystem models may thus be appropriate for examining the potential community effects of a deepwater lionfish fishery [15,64].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fishery removals are widely encouraged as the primary means for controlling lionfish densities 20,21 . High removal effort can control lionfish densities on local reefs 22,62,63 , but population models have indicated regional nGOM fishing intensity has been well below the levels estimated to cause recruitment overfishing 27,55,64 www.nature.com/scientificreports www.nature.com/scientificreports/ landings increased c. 8X between 2015 to 2017, it was estimated that an approximate 100X increase in fishery removals from 2015 levels would be necessary to achieve a fishing mortality rate that would substantially reduce regional lionfish biomass 27 . Moreover, the strong declines on high-density reefs indicate population effects from removals may be mitigated by density-dependent population compensation.…”
Section: Discussionmentioning
confidence: 99%
“…More time will be necessary to understand how native communities will be affected by changes in the lionfish populations or the lionfish epizootic. Recent experimental lionfish removal studies have indicated declines in lionfish density result in a mixture of positive 62,75 , negative 65 , and undetectable 22,63 effects on native prey and competitor fish biomass. Possible explanations for the lack of expected, positive results include the following: recruitment and succession dynamics operate on longer time scales than could be observed in the study period; ecological damages persist after lionfish are removed 4,76 ; the density of undetected lionfish in the system is greater than the critical density to achieve community-level benefits 40,51 ; or, ecological benefits are confounded by natural 65 or anthropogenic 22 disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than many fisheries where removal efficiency is <10% [6365], but considerably lower than the >85% removal efficiency for spearfishing lionfish on nGOM artificial reefs [46]. Given spearfishing can reduce lionfish densities in areas frequented by divers [6668] and spearfishing fisheries have caused severe depletion of other reef fishes [6971], we expect spearfishing to remain the most efficient and cost-effective method for removing lionfish biomass at depths <40 m. Removal efficiencies and uncaptured lionfish will need to be considered when evaluating the potential community benefits offered by lionfish trapping as lionfish removals do not necessarily translate into ecological benefits [14,72,73] given lionfish predation [62,74], growth [53,75], and colonization [14,73,76] rates are controlled via density-dependent feedbacks. Ecosystem models may be appropriate for examining the potential community effects of a deepwater lionfish fishery [15,77].…”
Section: Discussionmentioning
confidence: 99%